A Rare Presentation of Lymphoma of the Cervix with Cross-Sectional Imaging Correlation. (17th April 2014) - Korivi, Brinda Rao; Jensen, Corey T.; Patnana, Madhavi; Patel, Keyur P.; Bathala, Tharakeswara K.
Abstract : Non-Hodgkin's lymphoma of the cervix is an extremely uncommon entity, with no standard established treatment protocol. A 43-year-old asymptomatic female with a history of dual hit blastic B-cell lymphoma/leukemia in complete remission presented with an incidental cervical mass, which was initially felt to represent a cervical fibroid on computed tomography (CT). It was further evaluated with ultrasound, biopsy, and positron emission tomography-computed tomography (PET-CT), which demonstrated a growing biopsy-proven lymphomatous mass and new humeral head lesion. The patient was started on chemotherapy to control the newly diagnosed humeral head lesion, which then regressed. She then underwent radiation to the cervix with significant improvement in the cervical lymphoma. A review of cross-sectional imaging findings of lymphoma of the cervix is provided, including how to differentiate it from other more common diseases of the cervix. Clinical awareness of rare cervical masses such as lymphoma is very important in order to achieve timely diagnosis and appropriate treatment.